2000
DOI: 10.1038/77131
|View full text |Cite
|
Sign up to set email alerts
|

Defects in TCIRG1 subunit of the vacuolar proton pump are responsible for a subset of human autosomal recessive osteopetrosis

Abstract: Osteopetrosis includes a group of inherited diseases in which inadequate bone resorption is caused by osteoclast dysfunction. Although molecular defects have been described for many animal models of osteopetrosis, the gene responsible for most cases of the severe human form of the disease (infantile malignant osteopetrosis) is unknown. Infantile malignant autosomal recessive osteopetrosis (MIM 259700) is a severe bone disease with a fatal outcome, generally within the first decade of life. Osteoclasts are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
448
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 625 publications
(456 citation statements)
references
References 19 publications
4
448
0
4
Order By: Relevance
“…V-ATPases are proton-translocating transporters that become enriched in ruffled borders of polarized osteoclasts and mediate acidification of the resorptive space [24,25]. A lack of V-ATPases in the ruffled border results in impaired bone resorption, and in humans and mouse models, a malignant form of osteopetrosis [26][27][28][29]. Figure 5B shows confocal sections at the base of either a control-transfected (top panels) or Tm-4 overexpressing (bottom panels) cell.…”
Section: Overexpression Of Tropomyosin 4 Results In Altered F-actin Smentioning
confidence: 99%
“…V-ATPases are proton-translocating transporters that become enriched in ruffled borders of polarized osteoclasts and mediate acidification of the resorptive space [24,25]. A lack of V-ATPases in the ruffled border results in impaired bone resorption, and in humans and mouse models, a malignant form of osteopetrosis [26][27][28][29]. Figure 5B shows confocal sections at the base of either a control-transfected (top panels) or Tm-4 overexpressing (bottom panels) cell.…”
Section: Overexpression Of Tropomyosin 4 Results In Altered F-actin Smentioning
confidence: 99%
“…Furthermore, mutations in the TCIRG1 gene, which encodes for the human a3 subunit, have been reported in patients affected by infantile malignant osteopetrosis, a heterogeneous autosomal recessive disorder of bone metabolism (12)(13)(14)(15). In addition, recent study has shown that V 0 subunit d2 is important for osteoclast fusion (37).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mutations in the human TCIRG1 gene, which encodes for a osteoclast specific V-ATPase subunit, a3, results in infantile malignant osteopetrosis, thus substantiating the importance of V-ATPase in osteoclastic bone resorption (12)(13)(14)(15). The structural and functional analyses of the V-ATPase complex in osteoclasts might facilitate the development of anti-resorptive agents targeting specifically the osteoclast V-ATPases (16).…”
mentioning
confidence: 99%
“…Cross-linked bone collagen and the peptides containing cross-links used to estimate the rate of bone resorption in serum or urine are not degraded by proteinases. A mutation in the Atp6i also causes an osteopetrosis in human [17,18].…”
Section: Osteoclast Physiologymentioning
confidence: 99%